Policy of Western States in Central Asia: The Role of Rare-Earth Metals - S. S. Zhiltsov (Проблемы постсоветского пространства)
After the collapse of the USSR, the policy of the Western states towards Central Asia was focused on the issues linked to the expansion of trade and economic relations, gaining access to hydrocarbon resources of the regional countries and organizing their reliable export to foreign markets. In recent years, due to changes in technological development, the Western countries have increased their interest in rare-earth metals. Competition aimed at getting control over explored and prospective deposits is unfolding in different regions of the world. One of the promising areas with significant reserves of rare-earth metals is Central Asia. For this reason, in the last few years the USA, the EU, Great Britain and other countries have become increasingly interested in the region. The West is pursuing an active policy course towards Central Asian states. Such an approach is aimed not so much at developing the countries of the area as at expanding the presence of the West and reorienting the foreign policy course of the regional states towards the interests of non-regional actors. The ultimate goal of the Western states is to gain control over the deposits of rare-earth metals, which are located in Central Asia. The article covers the main directions of the policy the Western states apply in the region and underscores the mechanisms they use to promote their interests in gaining access to promising deposits of rare-earth metals. At the same time, the countries of the region generally welcome the Western policy, believing that it will attract additional investments into their economies. In turn, some influential and rich Western states along with companies they support exert pressure on Central Asian countries, seeking the most favorable conditions for themselves in the development of deposits and control over the resulting resources. The article concludes that Russia and China are competing with the Western states in Central Asia for getting access and gaining control over the deposits of rare-earth metals.